Learning from peers: Collaborative learning to improve instructional practice - Ann Rosnida Mohd Deni, * (2012)
A Teacher Inquiry Community for staff development was formed between teachers of language programmes at a private university in Malaysia to explore the learning process within a community of teachers who took inquiry as a stance to improve their instructional practice. Data for the study was collected through participant observation, audio recorded interactions, in-depth interviews, analyses of documents and qualitative questionnaires. Ten language teachers from various university programmes within a Malaysian private higher educational institution took part in this study. Analysis of data reveals the following: i) teacher learning in the teacher inquiry community was influenced by the dilemma raised, the protocol utilised and the evidence of practice shared; ii) new knowledge about teaching surfaced through sharing and deprivatisation of practice at various points during each session; iii) teachers would go through cycles of inquiries and individual and group reflection during each session and, iv) learning took place within these cycles and resulted in the acquisition of new knowledge and skills, changes in teachers’ perspectives, new understanding about role as teacher, and reinforcement of past beliefs about teaching and learning.